AKIN10, a representative Arabidopsis SNF1‐related protein kinase 1 (SnRK1), phosphorylates and downregulates plant HMG‐CoA reductase. Issue 8 (3rd April 2017) - Robertlee, Jekson; Kobayashi, Keiko; Suzuki, Masashi; Muranaka, Toshiya
Abstract : HMG‐CoA reductase (HMGR) is a key enzyme in the mevalonate pathway for sterols and cytosolic isoprenoid production. Although HMGR kinases from spinach, barley, and cauliflower tissues have been strongly suggested as members of SNF1‐related protein kinases 1 (SnRK1), the phosphorylation and inactivation of HMGR by plant SnRK1s has not been demonstrated. In this study, we elucidated that AKIN10, an Arabidopsis SnRK1, acts as an HMGR kinase. The recombinant AKIN10 phosphorylates and inactivates AtHMGR1S using recombinant GRIK1 as the AKIN10 activator. In contrast, AKIN10‐GRIK1 fails to inactivate AtHMGR1S‐S577A, suggesting that this is achieved through Ser577 phosphorylation. Moreover, phosphorylation is detected not only in AtHMGR1S but also in AtHMGR1S‐S577A, suggesting the presence of a novel regulatory mechanism of plant HMGR. Abstract :